Endoscopic Management of Anastomotic Strictures after Liver Transplantation - Dong Wook Lee; Hyeong Ho Jo; Juveria Abdullah; Michel Kahaleh (Clinical Endoscopy, 2016)
Endoscopic treatment of biliary strictures involving plastic stent placement has been used widely. The use of self-expandable metal stents (SEMSs) has been described for anastomotic strictures following liver transplantation (LT). This review aimed to assess and compare the efficacy of plastic stents with SEMS in LT patients. Information was retrieved regarding technical success, stricture resolution, the number of endoscopic retrograde cholangiography procedures, follow-up, immediate, and late complications. Eight studies involving plastic stents had a stricture resolution rate of 84.5%, with the rates ranging from 63% to 100%. These rates are comparable with the stricture resolution rate of 75% determined from six studies that involved 236 patients who received metal stents and the rates ranged from 53% to 81%. The observed success rate for metal stents used to manage post-LT anastomotic biliary strictures was below the reported rate for multiple plastic stents. Hence, the currently available metal stents should not be offered for the management of post-LT anastomotic biliary strictures.